PENGARUH KOMPENSASI FINANSIAL DAN KOMPENSASI-NON FINANSIAL TERHADAP KNERJA KARYAWAN DI RS MUHAMADIYAH BABAT - Darianto, Darianto; Mas'adah, Mas'adah; Mu'ah; Surya Ariefin, Mesra; Sayyid, Mokhtar (STIE Mahardhika, 2026)
This study aims to analyze the effect of financial and non-financial compensation on employee performance at Muhammadiyah Babat Hospital. Employee performance is a key factor in ensuring quality health services and patient satisfaction. This study uses a quantitative approach with an explanatory research method. Data were obtained by distributing questionnaires to hospital employees using proportional sampling techniques. Data analysis was performed using multiple linear regression with the help of SPSS. The results showed that financial compensation had a positive and significant effect on employee performance. Non-financial compensation was also found to have a positive and significant effect on employee performance. Simultaneously, financial and non-financial compensation significantly affect employee performance. These findings indicate that a balanced compensation policy between financial and non-financial aspects is very important in improving hospital employee performance. This study is expected to serve as a basis for hospital management in formulating sustainable human resource management strategies.